Role of Nurses in Health Needs of Refugees and Internally Displaced Peoples - Hawar Abdulrazaq Mohammedsadiq; Sana Thannon Ahmed; Saadia Kadhim MuhammedHassan (Hawler Medical University, 2019)
Background and objectives: Nurses working in refugee camps face to high basic health needs of these populations requiring a nursing role in this situation. The aim of this study was to explore the role of nurses in addressing the basic health needs of refugees and internally displaced peoples. Methods: In this cross-sectional study, 120 nurses from 26 camps in Duhok governorate/Iraqi Kurdistan were invited to participate in the study between September 15th and November 25th, 2017. Data was collected through the direct interview (investigator-administered self-reported technique) with the participants. The findings of the study were presented in descriptive statistics. Results: The mean age of nurses was 29.10 years old. The nurses participated in activities such as infection control activities (78.3%), health education campaigns (92.5%), breastfeeding education (84.2%), and nursing health care services (94.2%). Board of Relief and Humanitarian Affairs is a governmental body within the structure of Duhok governorate and is a key agent of basic needs of refugees. Conclusions: The study documented that a considerable percentage of nurses have participated in the nursing-based activities in refugee camps.